NAO Robots Help Children with Autism Develop Social Communication Skills - Jerrie Brooks (The Advocate, 2026)
Federal mandates ensure that children with autism spectrum disorder (ASD) are educated in the least restrictive environment; however, social communication deficits often leave these students on the periphery of the general education experience. While explicit instruction is necessary to build foundational social learning skills like joint attention and imitation, traditional human-led interventions can be unpredictable or overwhelming for students with ASD. This article explores using the NAO humanoid robot as a predictable, non-judgmental, and engaging instructional strategy to bridge this gap. By leveraging the robot’s autonomous programming—from basic motor imitation (like animal sounds and saluting the flag) to advanced sensory hooks and interactive literacy modeling—educators can create a safe space for social learning. Preliminary school-based applications suggest that the NAO robot serves as a "technological bridge" that transforms theoretical social robotics into a practical tool for improving social communication skills, engagement, and academic momentum in early elementary settings.
Keywords: autism; early childhood education; social communication skills; NAO humanoid robot